2018
DOI: 10.1016/j.jacc.2017.11.036
|View full text |Cite
|
Sign up to set email alerts
|

PET/MR Imaging of Malondialdehyde-Acetaldehyde Epitopes With a Human Antibody Detects Clinically Relevant Atherothrombosis

Abstract: BACKGROUND Oxidation-specific epitopes (OSEs) are proinflammatory, and elevated levels in plasma predict cardiovascular events. OBJECTIVES The purpose of this study was to develop novel positron emission tomography (PET) probes to noninvasively image OSE-rich lesions. METHODS An antigen-binding fragment (Fab) antibody library was constructed from human fetal cord blood. After multiple rounds of screening against malondialdehyde-acetaldehyde (MAA) epitopes, the Fab LA25 containing minimal nontemplated inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…The E06-scFv expressed in these mice lacks Fc effector functions of antibodies, and therefore, its impact was caused solely by blocking biological effects of OxPL. Translational applications of E06 or similar anti-OxPL antibodies to humans, as well as antibodies to other OSE 29,30 , in which more traditional IgG isotypes are more likely to be used, will need to decipher any potential additional roles of various Fc effector functions.…”
Section: Introductionmentioning
confidence: 99%
“…The E06-scFv expressed in these mice lacks Fc effector functions of antibodies, and therefore, its impact was caused solely by blocking biological effects of OxPL. Translational applications of E06 or similar anti-OxPL antibodies to humans, as well as antibodies to other OSE 29,30 , in which more traditional IgG isotypes are more likely to be used, will need to decipher any potential additional roles of various Fc effector functions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, if the developed diagnostic agents were to reach the clinics, the use of humanlike antibodies should limit the risk of immunogenicity, saving the time that would be required for humanization of murine antibodies. HuAbs, 174 humanized, or human antibody fragments 124,152,157,162,177,189 therefore represent a class of ligands that will be theoretically safer to transfer to the clinics.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Senders et al developed novel PET probes making use of an Fab, Fab LA25, obtained from an antibody library constructed from human fetal cord blood. 177 This antibody was selected against MDA-acetaldehyde (MAA) epitopes. Using PET/MRI, the authors observed an approximately 32% increase in 89 Zr-LA25 uptake in the abdominal aorta of atherosclerotic rabbits relative to nonatherosclerotic rabbits.…”
Section: Imaging Of Components From the Lesional Microenvironmentmentioning
confidence: 99%
“…During the process of LDL oxidation, various by-products are generated that have proinflammatory chemical modifications of lipid and protein moieties that are known as oxidation-specific epitopes (OSEs), which could signal dangerously high levels of inflammation in plaque [51]. Therefore, Senders et al [52] investigated the utility of a novel PET probe, 89 Zr-LA25, that targeted malondialdehydeacetaldehyde epitopes and found that 89 Zr-LA25 specifically co-localized to advanced and ruptured atherosclerotic plaques that had accompanying thrombi. Recent work by Sasaki and colleagues [53] has further demonstrated the potential of molecular imaging of oxLDL in atherosclerosis by developing a PET targeted probe, 64 Cu-3H3-scFv, targeting the B2-glycoprotein/oxLDL complex, with the probe showing colocalization to lipid deposits in atherosclerotic lesions in a rabbit model of hyperlipidemia.…”
Section: Emerging Targets For Radionuclide Imaging Of Atherothrombosismentioning
confidence: 99%